Efecto de la eficacia del gobierno sobre el crecimiento económico de Ecuador, periodo 1992-2021; mediante un modelo econométrico de series de tiempo. - Jaramillo Abad, Kevin (2024)
The Ecuadorian economy has experienced a slowdown in recent years, showing a growth rate of 1.7% in the second quarter of 2022 compared to the same period in 2021. In this context, the objective of this study is to examine the relationship between government effectiveness and economic growth in Ecuador during the period 1992-2021. Statistical and econometric techniques are employed to analyze data from the World Bank (WB) [2023] and Worldwide Governance Indicators (WGI) [2023], using variables such as per capita GDP and government effectiveness as dependent and independent variables, respectively. Additionally, control variables such as inflation, Human Development Index, and gross capital formation will be incorporated, estimated through a time series econometric model. The main results reveal a long-term close relationship between government effectiveness, inflation, and gross capital formation with economic growth, as well as a short-term relationship between inflation and economic growth. A significant causal relationship is identified from economic growth to government effectiveness, inflation, and gross capital formation, as well as from government effectiveness to economic growth. As a recommendation, policies aimed at promoting economic growth in Ecuador are suggested, focusing on strengthening government effectiveness through transparency measures, personnel training, and anti-corruption efforts.